Filipinos in Canada disturbing invisibility - Coloma, Roland Sintos; McElhinny,Bonnie; Tungohan, Ethel; Catungal, John Paul C.; Davidson, Lisa M. (Toronto, Canada University of Toronto Press, 2012)
"The Philippines became Canada's largest source of short- and long-term migrants in 2010, surpassing China and India, both of which are more than ten times larger. The fourth-largest racialized minority group in the country, the Filipino community is frequently understood by such figures as the victimized nanny, the selfless nurse, and the gangster youth. On one hand, these narratives concentrate attention, in narrow and stereotypical ways, on critical issues. On the other, they render other problems facing Filipino communities invisible.
This landmark book, the first wide-ranging edited collection on Filipinos in Canada, explores gender, migration and labour, youth spaces and subjectivities, representation and community resistance to certain representations. Looking at these from the vantage points of anthropology, cultural studies, education, geography, history, information science, literature, political science, sociology, and women and gender studies, Filipinos in Canada provides a strong foundation for future work in this area."--
Part I Difference and Recognition -- 1. Spectres of In/visibility: Filipina/o Labour, Culture, and Youth in Canada / Bonnie McElhinny, Lisa M. Davidson, John Paul C. Catungal, Ethel Tungohan, and Roland Sintos Coloma -- 2. Filipino Canadians in the Twenty-First Century: The Politics of Recognition in a Transnational Affect Economy / Eleanor Ty -- 3. Filipino Immigrants in the Toronto Labour Market: Towards a Qualitative Understanding of Deprofessionalization / Philip F. Kelly, Mila Astorga-Garcia, Enrico F. Esguerra, and the Community Alliance for Social Justice, Toronto -- My Folks / Carlo Sayo and Jean Marc Daga -- Part II Gender, Migration, and Labour -- SCRAP / Reuben Sarumugam and Bryan Taguba -- 4. The Recruitment of Philippine-trained Healthcare Professionals to Canada in the 1960s / Valerie G. Damasco -- 5. The Rites of Passage of Filipinas in Canada: Two Migration Cohorts / Josephine Eric -- 6. (Res)sentiment and Practices of Hope: The Labours of Filipina Live-in Caregivers in Filipino Canadian Families / Lisa M. Davidson -- 7. Debunking Notions of Migrant "Victimhood": A Critical Assessment of Temporary Labour Migration Programs and Filipina Migrant Activism in Canada / Ethel Tungohan -- 8. Toronto Filipino Businesses, Ethnic Identity, and Place Making in the Diaspora / Cesar Polvorosa, Jr. -- 9. Between Society and Individual, Structure and Agency, Optimism and Pessimism: New Directions for Philippine Diasporic and Transnational Studies / Leonora C. Angeles -- Part III Representation and Its Discontents -- Balikbayan Express / Celia Correa -- 10. Meet Me in Toronto: The Re-Exhibition of Artifacts from the 1904 Louisiana Purchase Exposition at the Royal Ontario Museum / Bonnie McElhinny -- 11. From the Pearl of the Orient to Uptown: A Collaborative Arts-Based Inquiry with Filipino Youth Activists in Montréal / Marissa Largo -- 12. Borrowing Privileges: Tagalog, Filipinos, and the Toronto Public Library / Vernon R. Totanes -- 13. Abject Beings: Filipina/os in Canadian Historical Narrations / Roland Sintos Coloma -- 14. Between the Sheets / Geraldine Pratt -- Part IV Youth Spaces and Subjectivities -- Colour Correction / Eric Tigley -- 15. Scales of Violence from the Body to the Globe: Slain Filipino Youth in Canadian Cities / John Paul C. Catungal -- 16. Kapisanan: Resignifying Diasporic Post/colonial Art and Artists / Christine Balmes -- 17. Educated Minorities: The Experiences of Filipino Canadian University Students / Maureen Grace Mendoza -- 18. "Mas Maputi Ako sa 'yo" ("I'm lighter than you"): The Spatial Politics of Intrarracial Colorism among Filipina/o Youth in the Greater Toronto Area / Conely de Leon -- 19. The Social Construction of "Filipino Studies": Youth Spaces and Subjectivities / Jeffrey P. Aguinaldo -- Part V Afterword -- 20. Contemplating New Spaces in Canadian Studies / Minelle Mahtani and David Roberts.
Includes bibliographical references and index.
Keywords: Filipinos -- Canada -- History; Filipinos -- Canada -- Social conditions; Filipinos -- Canada -- Economic conditions